The process of economic development - Cypher, James M. (Abingdon, Oxon : Routledge, 2014)
'The period since the publication of the third edition of The Process of Economic Development has been a time of immense change in the developing world. China, India and Brazil have enjoyed a period of huge economic growth while smaller countries such as Vietnam and Angola have also been subject to striking transformation. Environmental issues such as climate change have also had a huge impact, while issues of security in the Middle East and elsewhere have underlined the importance of natural resources and the ongoing forces of globalization.The fourth edition of this popular textbook has been updated to reflect the new challenges faced by developing countries across Asia, Latin America and Africa, while retaining its ever important emphasis on institutions, the importance of technology and the influence of global finance and business'--
'The fourth edition of The Process of Economic Development offers a thorough and up-to-date treatment of development economics. This landmark text will continue to be an invaluable resource for students, teachers and researchers in the fields of development economics and development studies. The new edition has been revised and updated throughout, reflecting the most recent developments in research and incorporating the latest empirical data, as well as key theoretical advances. The period since the publication of the third edition of The Process of Economic Development has been a time of immense change in the developing world. The period has seen huge economic growth in China, economic restructuring in India and the continuing impact of environmental issues such as climate change. The fourth edition reflects these developments, as well as including new material on the following: - transnational corporations - perspectives on structural change - gender and development - progress towards the Millennium Development Goals - aid and the least developed nations - the post debt crisis era and debt relief for Africa. Cypher's text remains the development economics text par excellence, as it takes a much more practical, hands-on view of the issues facing developing countries than other, overly mathematical texts. This book is unique in its scope and in the detailed attention it gives to the historical contexts that have influenced progress toward development. It is accessibly written both for students of economics and for those with an interest in the many aspects of development studies'--
Includes bibliographical references and index.
Keywords: Economic development